Synthesis of novel CoOx decorated CeO2 hollow structures with an enhanced photocatalytic water oxidation performance under visible light irradiation. Issue 32 (1st February 2017) - Fang, Siman; Li, Songsong; Ge, Lei; Han, Changcun; Qiu, Ping; Gao, Yangqin
Abstract : Cobalt oxide decorated octahedral ceria hollow structures (CoO x /CeO2 ) with various contents of CoO x nanoparticles were prepared via a simple chemical impregnation method. Abstract : Cobalt oxide decorated octahedral ceria hollow structures (CoO x /CeO2 ) with various contents of CoO x nanoparticles were prepared via a simple chemical impregnation method. The obtained samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), UV-Vis diffuse-reflectance spectroscopy (DRS), surface photovoltage spectroscopy (SPV) and transient photovoltage spectroscopy (TPV). The photocatalytic oxygen evolution via water oxidation was investigated for the as-prepared CoO x /CeO2 nanocage composites. The photocatalytic results indicate that the CoO x /CeO2 nanocage composite with 1 mol% CoO x shows the highest photocatalytic activity. The excellent photocatalytic activity can be attributed to the improved visible-light absorption of CoO x /CeO2 composites and the efficient separation of excited electron–hole pairs between CoO x and CeO2, which can effectively enhance the lifetime of charge carriers in the CoO x -modified samples and then improve the oxygen evolution activity. Cobalt oxide is expected to be an excellent water oxidation co-catalyst for semiconductor photocatalysts.